A Brief History of Knowledge Building - Marlene Scardamalia; Carl Bereiter (The Canadian Network for Innovation in Education (CNIE), 2010)
Knowledge Building as a theoretical, pedagogical, and technological innovation focuses on the 21st century need to work creatively with knowledge. The team now advancing Knowledge Building spans multiple disciplines, sectors, and cultural contexts. Several teacher-researcher-government partnerships have formed to bring about the systemic changes required to accommodate pedagogical innovations that range from elementary to tertiary education and require new forms of teacher education. This paper tracks the evolution of Knowledge Building, starting with research on "knowledge transforming," "intentional learning," and other processes leading to the development of expertise. It provides an account of how the first networked collaborative learning environment was developed to support such processes and next-generation research and development to advance education for innovation and knowledge creation.